The natural components of agricultural development in northwest Libya and major problems and challenges of sustainability - Aouen, Matog Ali; Al-Dulaimi, Ahmed Jassam (Journal of Tikrit University for Humanities, 2020)
This research aims to identify and analyze the natural geographical components available in northwest Libyan their suitability to achieve sustainable agricultural development, as well as, to Find out the main challenges facing to achieve this goal. The documentary and descriptive approaches were adapted in this research to get the data needed, and it was supported by conducting some field studies related subject of research in order to obtain some of required missing and unavailable information. The results shows that although 5 the most of natural geographic components of the area are considered appropriate to achieve sustainable agricultural development. Nonetheless, there are many natural and human challenges to reach this goal , which means that these challenges must be overcome, in order to reach future guaranteed results in this context. The research concluded with a set of important recommendations, that can be used when starting to plan plans for sustainable development programs in the region.